Adolescent Obesity and Its Association with Diet Quality and Cardiovascular Risk Factors - Yilmaz, Feray Cagiran; Cagiran, Derya; Ozcelik, Ayse Ozfer (Taylor & Francis Inc, 2019)
Objective: This study aimed to evaluate the adolescent obesity and its association with Mediterranean Diet Quality Index (KIDMED) and cardiovascular risk factors in adolescents.Method: This cross sectional study included 95 adolescents aged between 10 and 18 who visited a Primary Health Service Center in Turkey. Participants' biochemical parameters, anthropometric measurements and blood pressures were measured. The level of adherence to Mediterranean Diet was evaluated by a clinical questionnaire, the Mediterranean Diet Quality Index for children and adolescents (KIDMED).Results: Overweight adolescents had significantly higher systolic blood pressure, diastolic blood pressure, total cholesterol, very low-density lipoprotein cholesterol, low-density lipoprotein cholesterol, triglycerides, hemoglobin A1c, C-reactive protein, alanine aminotransferase, than normal-weight adolescents. Overweight/obese subjects also had significantly lower HDL cholesterol than normal-weight subjects. Results indicated that 60.0% of the adolescents had a low quality diet, 34.7% had a mid-quality/needs-improvement diet, and 5.3% had an optimal quality diet. No association was found between diet quality and obesity and cardiovascular risk factors.Conclusion: Overweight and obese children are strongly associated with multiple cardiovascular risk factors. To avoid health problems arising from obesity, adolescents should refer to global solutions. Mediterranean diet is a good measure against adverse cardiovascular risk factors in adolescence.
Keywords: Mediterranean diet; cardiovascular risk factors; adolescents; KIDMED